Karl Polanyi and economics: Polanyi's pendulum in economic science - Mark Kretschmer (OrdnungsPolitisches Portal (OPO), 2019)
Since the crisis of 2008 the liberal market order has been challenged by several (populist) social movements and has become object of political regulation. Whereas in the late 70s and early 80s politics tend to deregulate the market, nowadays deregulation seem to be a synonym for the negative externalities of a free global market. Following Polanyi (The Great Transformation, 1944), societies with market market economies tend to experience a double movement - the Polanyi's Pendulum - between phases in which the policies are designed to restrict the markets or liberalize them. This paper raises the question if these indicated changes have an impact on the economic research topics. Referring to modern Varieties-of-Capitalism literature bibliometric data of the period between 1950 and 2015 are used to analyze if there is a Polanyi's Pendulum within the economic literature. Looking for specific key words, e.g. liberalization, and using correlation analyses and time-series regressions it is possible to determine changes of the topics economists worked on and to identify those economic macro-forces that have been driven these changes. The political development in recent years can be considered as a new swing of Polanyi's pendulum. Economics itself is part of the double movement. A second look at Polanyi's might be fruitful to face present challenges better equipped.
Keywords: 330; political economy; double movement; bibliometry; Varieties of Capitalism; economics